UMPSA hosts Community Lecture 2024 Organisational Security vs Leadership Integrity - Mohammad Ilzam, Jamat; Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 12 December 2024 – The Community Lecture programme titled “Organisational Security vs Leadership Integrity” held at Dewan Astaka, UMPSA Gambang Campus, recently served as a platform for knowledge-sharing with students and staff to raise awareness on issues of leadership integrity, security, crisis management with strong leadership, and leaders as determinants of success.